Perbandingan Latihan Two Kick One Pull dengan Controlled Breaststroke terhadap Stroke Rate Gaya Dada - Azzah Shabira Putri; Heru Miftakhudin; Ferry Yohannes Wattimena (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
This study aims to find out, 1) The effect of exercise using two kick one pull on the stroke rate of breaststroke, 2) The effect of exercise using controlled breaststroke on the stroke rate of breaststroke, 3) The difference in stroke rate of breaststroke through the method of two kick one pull exercise with controlled breaststroke. This research method uses an experimental method with research using two groups "pre- test and post-test design. The subject of this study was 16 Ekoatics Swimming Club swimmers taken with purposive sampling techniques. Data collection was carried out by conducting a 50-meter breaststroke test by taking the number of stroke rates using a special stroke rate stopwatch. Data analysis was carried out using a dependent and independent "t-test" with a significant level of 0.5. The results of the study: 1) training using Two Kick One Pull, obtained t count 3.44 greater than t table 2.365, then it means that H0 was rejected and H1 was accepted, meaning there was a significant increase, 2) exercise using Controlled Breaststroke, t count 2.75 was obtained greater than t table 2.365, then H0 was rejected and H1 was accepted, meaning there was a significant increase, 3) comparing the final test results of the two exercise methods, the results were obtained, t count 1.74 was smaller than t table 2.144, meaning that there was no difference between the Two Kick One Pull exercise and the Controlled Braststroke exercise. However, based on the average final test results of Two Kick One Pull 35.5 and Controlled Breaststroke with 40.12, there is a difference that the average number of Controlled Breaststroke is larger.